Religions in southern Africa Customs - Shemer M; South Africa (South Africa: Awareness Pubhishing Group (Pty) Ltd., 2013)
A basic introduction to African independent churches, and some of the customs of their followers. this book looks at their healing ceremonies, their worship and batism practices, and their traditional cloyhing, marriages and funerals.
African Independent Churches
Junior Non-Fiction-; Juvenile literature